Evolution of the freshwater provisioning services under climate change and vegetation restoration influences. (October 2022) - Li, Ping; Yang, Dawen; Chaubey, Indrajeet; Su, Xiaoling; Jiang, Yanan
Highlights: Freshwater provisioning decreased in the Yellow river basin during last 57 years. Increased annual precipitation significantly improved the freshwater provisioning. Freshwater provisioning decreased impacting by vegetation restoration after 1999. Freshwater provisioning service negatively impacted by the raised slope. Abstract: The freshwater provisioning ecosystem services are important and complicatedly affected by climate change and human activities. The well-known Grain for Green Program (GGP) implemented in the Yellow River Basin (YRB) of China, greatly modify the flow patterns and result cascading effects on the freshwater provisioning services of watershed ecosystem. Studies about the impacts of climate and land use changes on streamflow increased rapidly in recent years; however, the evolution characteristic of the freshwater provisioning services under climate change and vegetation restoration is poorly understood. Based on an index-based ecosystem service approach, the annual freshwater provisioning index (FWPI) was calculated and evolution of the freshwater provisioning services were analyzed from 1958 to 2014 for nine watersheds in the YRB. According to a coupled ecohydrological model (CLM-GBHM) developed in the YRB, two vegetation scenarios consisting of fixed leaf area index (LAI) in 1982 and remote-sensed LAI among 1982–2014were established and the annual FWPI under both scenarios were simulated. The respective influence of vegetation restoration and climate on the freshwater provisioning services were finally quantitatively analyzed. The results show that the annual FWPI had a general decrease in most of watersheds in the past 57 years. The increased precipitation during 2000–2014 significantly improved the freshwater provisioning services by 0.8 %–21.3 % among 9 watersheds in comparison with those during 1980–1999, considering the respective impact of climate change. The restored vegetation after the GGP carried out since 1999 had a negative influence on the freshwater provisioning services in the YRB. The mean annual FWPI obviously reduced by −11.9 % and −3.6 % in the upper YRB and the entire basin, respectively, and it reduced by −2.4 %∼−5.8 % in five tributary watersheds during 2000–2014. A significant positive correlation between the mean annual FWPI(S1-S2) which denoting the difference between FWPI under two vegetation scenarios (S1, S2), and the average slope was observed (R 2 = 0.52 and p < 0.05), indicating the negative effect of the raised slope on the freshwater provisioning services. Above results suggest that the precipitation is one critical climate factor of enhancing the freshwater provisioning services, whereas the negative influence of the vegetation restoration and slope changes on the freshwater provisioning should be considered when implementing the GGP for enhancing other hydrological services such as soil erosion control and the flood regulation in different river basins. Results from this study would provide scientific insights in enhancing ecology protection and sustainable utilization of water resources of watershed ecosystems..